Analysis of changes in mangrove land cover on the north coast of Aceh Besar - Kamisnuddin Kamisnuddin; Muhammad Rusdi; Muhammad Irham; Faisal Abdullah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
The use of Geographic Information Systems (GIS) to generate digital data that provides information on the characteristics of an area and describes changes in land cover that can be used in a more effective and efficient sustainable manner. This study aims to analyze the mangrove land cover of the north coast of Aceh Besar over the last three decades, namely 2000, 2010, and 2020 in the Baitussalam sub-district, Mesjid Raya sub-district and Seulimeum sub-district. The research was conducted from June 2022 to September 2022 at the GIS Laboratory, Faculty of Marine and Fisheries, Syiah Kuala University. The research was conducted using a Geographic Information System (GIS) that utilizes high-resolution satellite imagery from Google Earth Pro. Mangrove land was digitized visually on screen, then data processing was carried out, and spatially analyzed. The results of the analysis of changes in mangrove land cover in the research area show that the Baitussalam and Mesjid Raya sub-districts had a decreasing trend of mangove land between 2000 and 2010 and subsequently there was an increase in mangrove land cover from 2010 to 2020. Meanwhile, Seulimeum sub-district experienced a decreasing trend of land cover in 2000 until 2020. The decline in the trend of mangroves in various places is caused by the growth of the population using mangrove land as residential area. While the increase in mangove land cover was due to the success of reforestation and pond land conversion. The results conclude that the mangrove land cover on the north coast of Aceh Besar is relatively stable with an increasing trend of growth.Keywords:Land coverMangroveHigh resolution googleHistorical imageryGoogle earth proDigitize